Impact of Farmer Producer Organisations on organic chilli (Capsicum frutescens) production in Telangana - H, MANASWI B; KUMAR, PRAMOD; P, PRAKASH; KAR, AMIT; ANBUKKANI, P; JHA, G K; RAO, D U M (The Indian Journal of Agricultural Sciences, 2019)
There has been a substantial improvement in the performance of Farmer Producer Organisations (FPOs) in India in several aspects including access to technologies, markets, and value addition to agricultural produce. In this paper, an in-depth analysis has been done to understand the performance of FPOs for organic chilli in Indian state of Telangana based on the primary data collected from 60 farmers associated with FPOs and 60 non-FPO farmers from Siddipet and Janagaon, Telangana. The study employed empirical techniques, viz. tobit model, decomposition analysis and marketing efficiency to evaluate the impact of FPOs. The findings indicate that the input use in production of chilli was much less for the members of FPOs due to adoption of low inputs organic farming practices. Despite a lower yield, the members could realize 13.86% higher gross returns primarily attributed to FPOs providing access to technology and markets. The farmers in the study regions were following three marketing channels for disposal of their produce. The channel that involved FPOs with member farmers on the one end and consumers on the other is found to have the highest marketing efficiency in organic chilli.